Prion Strains Differ in Susceptibility to Photodynamic Oxidation - Kostelanska, Marie; Holada, Karel (Molecules (Basel, Switzerland), 2022)
Prion disorders, or transmissible spongiform encephalophaties (TSE), are fatal neurodegenerative diseases affecting mammals. Prion-infectious particles comprise of misfolded pathological prion proteins (PrPTSE). Different TSEs are associated with distinct PrPTSE folds called prion strains. The high resistance of prions to conventional sterilization increases the risk of prion transmission in medical, veterinary and food industry practices. Recently, we have demonstrated the ability of disulfonated hydroxyaluminum phthalocyanine to photodynamically inactivate mouse RML prions by generated singlet oxygen. Herein, we studied the efficiency of three phthalocyanine derivatives in photodynamic treatment of seven mouse adapted prion strains originating from sheep, human, and cow species. We report the different susceptibilities of the strains to photodynamic oxidative elimination of PrPTSE epitopes: RML, A139, Fu-1 > mBSE, mvCJD > ME7, 22L. The efficiency of the phthalocyanine derivatives in the epitope elimination also differed (AlPcOH(SO3)2 > ZnPc(SO3)1-3 > SiPc(OH)2(SO3)1-3) and was not correlated to the yields of generated singlet oxygen. Our data suggest that the structural properties of both the phthalocyanine and the PrPTSE strain may affect the effectiveness of the photodynamic prion inactivation. Our finding provides a new option for the discrimination of prion strains and highlights the necessity of utilizing range of prion strains when validating the photodynamic prion decontamination procedures.
Keywords: photodynamic; prionové nemoci; organokovové sloučeniny; Indoles; protein folding; prion; singlet oxygen; ovce; strain; prion inactivation; Photosensitizing Agents; fotosenzibilizující látky; TSE; Singlet Oxygen; fotochemoterapie; mozek; Mice; prionová bílkovina; skot; Oxidation-Reduction; Prion Diseases; Prion Proteins; Brain; PrP; zvířata; Humans; Organometallic Compounds; Photochemotherapy; Cattle; sbalování proteinů; myši; indoly; oxidace-redukce; Sheep; PDI; phthalocyanine; singletový kyslík; Protein Folding; lidé; Animals